Omega-3FAs Can Inhibit the Inflammation and Insulin Resistance of Adipose Tissue Caused by HHcy Induced Lipids Profile Changing in Mice - Li, Jing; Zhang, Heng; Dong, Yongqiang; Wang, Xian; Wang, Guang (Frontiers in Physiology, 2021)
The adipose Nod-like receptor protein 3 (NLRP3) inflammasome initiates insulin resistance, but the mechanism of adipose inflammasome activation remains elusive. In this study, Homocysteine (Hcy) is revealed to be participating in insulin resistance via a NLRP3 inflammasome related process. Hcy-induced activation of NLRP3 inflammasomes were observed in adipose while insulin resistance formation in vivo. Give the experimental animal model a high Omega-3 fatty acids diet would change the serum and adipose lipids profile, and may in this is the way Omega-3 fatty acids improve the adipose inflammation and attenuates the insulin resistance.